Relationships Between Smoking and Sleep Problems in Black and White Adolescents - Bellatorre, Anna; Choi, Kelvin; Lewin, Daniel; Haynie, Denise; Simons-Morton, Bruce (Sleep (New York, N.Y.), 2017)
Abstract Study Objectives: The relationship between sleeping and smoking during adolescence remains unclear and is likely complex. We aim to evaluate the longitudinal reciprocal associations between sleep problems, sleep duration, and smoking among non-Hispanic white (NHW) and non-Hispanic black (NHB) youth. Design: Prospective cohort study Setting: NEXT Generation Health Study Participants: A national sample (N = 1394) of NHB and NHW 10th graders were surveyed annually between 2009 (Wave 1) and 2012 (Wave 3). Interventions: N/A Measurements and Results: Past 30-day smoking, chronic difficulty falling asleep, recent difficulty falling asleep, difficulty staying asleep, and weekday and weekend sleep duration were measured at each wave. Using structural equation models, we observed significant autocorrelations over time for sleep problems and sleep duration. We found significant reciprocal, prospective relationships between smoking and sleep problems. The strengths of the relationships differed by race, with a stronger association between sleep problems and subsequent smoking for NHB than NHW youth. Conversely, a stronger association between smoking and subsequent sleep problems for NHW than NHB youth was observed. These association were independent of demographics, snoring or sleep apnea, body mass index, depressive symptoms, alcohol use, and soda consumption. Conclusions: Reciprocal and prospective relationships exist for youth smoking and sleep problems and duration in both NHW and NHB youth. Further research is needed to unravel the complex relationship between the direct effects of nicotine, lifestyle choices that may link smoking and sleep problems, and racial differences.